2014
DOI: 10.5005/jp-journals-10024-1601
|View full text |Cite
|
Sign up to set email alerts
|

Medical Emergency Management among Iranian Dentists

Abstract: To successful control of medical emergencies in the dental office, dentists must be prepared to recognize and manage a variety of such conditions. In addition to dentist's knowledge and skill, availability of necessary equipments and trained staff is also of critical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Syncope was one of the most common medical emergencies in the current study, which was consistent to the studies from multiple countries. [2,7,10] It is suggested that dentists should pay more attention to prevention, early diagnosis of these common but less fatal adverse events, and be prepared with pain and anxiety relief methods for effective management. [5,[11][12][13][14] In the current study, hypoglycemia (30.3%) and…”
Section: Discussionmentioning
confidence: 99%
“…Syncope was one of the most common medical emergencies in the current study, which was consistent to the studies from multiple countries. [2,7,10] It is suggested that dentists should pay more attention to prevention, early diagnosis of these common but less fatal adverse events, and be prepared with pain and anxiety relief methods for effective management. [5,[11][12][13][14] In the current study, hypoglycemia (30.3%) and…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study 32 evaluated patients' perceptions of ME in Dentistry and their expectations for dental surgeon' management, noting high patient expectations regarding dentists' general medical knowledge. Nevertheless, many studies support the lack of preparation of students 23,26,[33][34][35] and professionals [4][5][6][7][8][9][10][11][12][13][14] in managing ME, concluding that the subject should be addressed more deeply in dental education 11,23 , and for graduate dentists, refresher courses and workshops should be more frequently considered 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In such situations, professionals and their teams need to be confident and up to date with their skills in order to provide initial treatment of quality 3 . Despite the consensus on the importance of training dental surgeon in this subject, several national [4][5][6][7] and international studies [8][9][10][11][12][13][14] show unsatisfactory results by demonstrating low knowledge and confidence of professionals in managing ME and first aid.…”
Section: Introductionmentioning
confidence: 99%
“…Felmérések szerint csak a fogorvosok 20,8%-a tudott adekvát diagnózist felállítani [13], és csak kevesebb, mint 60%-uk tudott megfelelő újraélesztést végrehajtani [19]. Sürgősségi felszerelés csak a kérdezettek egynegyedénél volt található, az is hiányosan [38].…”
Section: Eredményekunclassified